Strategi Radio Republik Indonesia Surabaya Menarik Minat Pendengar Dalam programa 4 Tanjung Perak - Kumala, Asri dinda Septya; Murtadlo , Athok (LPPM Stikosa-AWS, 2024)
The identification of the problem in this study is how the strategy of Radio Republik Indonesia (RRI) Surabaya attracts listeners in Programa 4 Tanjung Perak. The identification of the problem is then elaborated again with a detailed discussion in several problem formulations, namely how does the strategy of Radio Republik Indonesia Surabaya attract listeners in Programa 4 Tanjung Perak?. This type of research is descriptive qualitative with the research approach used is mass communication. The informants of this research were the head of administration, the head of division of Programa 4 Tanjung Perak, the announcer of Programa 4 Tanjung Perak and the listeners of Programa 4 Tanjung Perak. Observation, interviews and documentation were used as data collection methods. Data analysis techniques used in three steps are data reduction, data presentation and conclusion drawing. The results of this study indicate that the Programa 4 Tanjung Perak broadcast is a broadcast that contains local culture, which is transmitted in the form of art through music, traditional musical instruments and messages from cultural experts. Radio is a digital media tool for disseminating information while Progama 4 Tanjung Perak acts as a form of message which then becomes an intermediary between disseminating information and receiving information about local culture. Radio Republik Indonesia (RRI) Surabaya's strategy to attract listeners is to use.